2020
DOI: 10.1186/s12964-020-00539-4
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated analysis reveals critical glycolytic regulators in hepatocellular carcinoma

Abstract: Background Cancer cells primarily utilize aerobic glycolysis for energy production, a phenomenon known as the Warburg effect. Increased aerobic glycolysis supports cancer cell survival and rapid proliferation and predicts a poor prognosis in cancer patients. Methods Molecular profiles from The Cancer Genome Atlas (TCGA) cohort were used to analyze the prognostic value of glycolysis gene signature in human cancers. Gain- and loss-of-function studies were performed to key drivers implicated in hepatocellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…( 61 ) A neutralizing antibody to OPN suppresses the stem‐like phenotype in HCCLM3 cells. ( 60 ) In Huh7 and HepG2 cells, OPN overexpression increases cell proliferation, ( 62 ) stem‐like properties, ( 60 ) glycolysis, ( 63 ) autophagy, and resistance to chemotherapy. ( 64 ) Conversely, SPP1 knockdown in HCCLM3 and HepG2 cells decreases proliferation, migration, and sensitivity to chemotherapy.…”
Section: Opn and Hccmentioning
confidence: 99%
“…( 61 ) A neutralizing antibody to OPN suppresses the stem‐like phenotype in HCCLM3 cells. ( 60 ) In Huh7 and HepG2 cells, OPN overexpression increases cell proliferation, ( 62 ) stem‐like properties, ( 60 ) glycolysis, ( 63 ) autophagy, and resistance to chemotherapy. ( 64 ) Conversely, SPP1 knockdown in HCCLM3 and HepG2 cells decreases proliferation, migration, and sensitivity to chemotherapy.…”
Section: Opn and Hccmentioning
confidence: 99%
“…However, the predictive ability of single-gene biomarkers is limited in RCC prognosis analysis and multiple-genes signature maybe a better strategy [ 16 ]. So far, only four studies have established the glycolytic risk signature in lung adenocarcinoma [ 17 ], endometrial cancer [ 16 ], hepatocellular carcinoma [ 18 ] and bladder cancer [ 19 ]. Therefore, to explore the potential roles of glycolytic metabolism and glycolysis-related genes in RCC, a series of bioinformatic analyses were performed through TCGA database (609 samples).…”
Section: Introductionmentioning
confidence: 99%
“… 38 Lu et al found that HSD17B13 was a tumor suppressive gene that inhibits HCC cell glycolysis as revealed by glucose utilization, lactate production, and extracellular acidification ratio. 39 PON3 is a member of Paraoxonase (PON) proteins primarily expressed in the liver, its expression and specific activities were found to negatively correlate with several inflammatory disorders and served as a prognostic predictor in HCC. 40 Song et al identified AMDHD1 was as a novel tissue-specific gene in human and mouse liver tissues.…”
Section: Discussionmentioning
confidence: 99%